Structural analysis of a rabbit hemorrhagic disease virus binding to histo-blood group antigens - Leuthold, Mila; Dalton, Kevin P.; Hansman, Grant S. (Journal of virology, 2015)
Rabbit hemorrhagic disease virus (RHDV) is a member of the Caliciviridae family (Lagovirus genus). RHDV is highly contagious and attaches to epithelial cells in the digestive or respiratory tract, leading to massive lesions with high mortality rates. A new variant of RHDV (termed RHDVb) recently has emerged, and previously vaccinated rabbits appear to have little protection against this new strain. Similar to human norovirus (Caliciviridae, Norovirus genus), RHDV binds histo-blood group antigens (HBGAs), and this is thought to be important for infection. Here, we report the HBGA binding site on the RHDVb capsid-protruding domain (P domain) using X-ray crystallography.
Accepted manuscript posted online 10 December 2014
Gesehen am 18.06.2020